Himalayan Blue Pine Deduced Precipitation Record from Cold Arid Lahaul–Spiti, Himachal Pradesh, India - Misra, Krishna G.; Singh, Vikram; Yadava, Akhilesh K.; Misra, Sandhya; Maurya, Ravi S.; Vishwakarma, Sadhana (Frontiers in Earth Science, 2021)
Ecologically Himalayan blue pine (Pinus wallichiana A. B. Jackson) is the most sensitive tree-species found across the high mountain ranges of Himalaya with deciphering tree-line for the region. Earlier studies showed the potential of Himalayan blue pine to reconstruct the past climate for extending observational data back to the centuries from orography-dominated Himalaya. However, tree-growth of the blue pine is largely found modulated by temperature in the western Himalayan region. In the present study, we attempted the first time to develop precipitation records using Himalayan blue pine chronology from cold arid Lahaul–Spiti, Himachal Pradesh, India. The blue pine chronology extends back to AD 1578 and showed significant relationship with the climatic variables. The bootstrap correlation analyses revealed previous year December to current year July precipitation plays significant role in tree-growth advancements. The previous year December to current year July (pDcJuly) precipitation has been reconstructed back to the AD 1730 for the Lahaul–Spiti region. The recorded individual and multi-year periods of low and high precipitation are consistent with existing hydro-climatic records from the western Himalaya. The five driest and wettest individual years are 1732, 1737, 1970, 2008, 1785, and 1730, 1771, 1758, 1734, 1736, respectively. The spatial correlation between gridded precipitation and reconstructed pDcJuly precipitation is significant for the region close to the sampling site. The study based on the Himalayan blue pine tree-ring chronology addressed its dendroclimatic utility for the semi-arid Lahaul–Spiti region and would be valuable to understand climatic variability over the past three centuries. The strong resemblance of the species with the Himalayan cedar growth patterns showed its promising viability to develop a network of multispecies for more robust climatic reconstruction in the future.